Dynamics of Heart Rate Variability in Children with Systolic Myocardial Dysfunction Under the Influence of Therapy - E.L. Akhnazariants (Zaslavsky O.Yu., 2014)
The aim of the research was to study the dynamics of changes in heart rate variability in children with myocardial pathology depending on the type of therapy. The study involved 84 children and adolescents of both genders aged 11-18 years with systolic myocardial dysfunction in various diseases of the heart, of which 42 children received pathogenetic therapy with angiotensin converting enzyme inhibitors for 3 months and 42 - drugs with cardiometabolic action for 30-45 days, repeated courses twice a year. Evaluation of heart rate variability was performed by the results of bifunctional daily monitoring of electrocardiographic and blood pressure monitoring using the apparatus ES-3N/AVR with Сardiospy software of Labtech company in accordance with standards developed by the Working Group of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology. It was found that in dynamics of the observation 48 % of children receiving pathogenetic therapy reported increased activity of the parasympathetic autonomic nervous system, which is accompanied by normalization of ejection fraction. And 52 % of children receiving metabolic therapy - increased activity of the sympathetic autonomic nervous system, associated only with a trend toward ejection fraction normalization. Due to this, children with systolic myocardial dysfunction of any origin should receive pathogenetic therapy with angiotensin converting enzyme inhibitors.